Perspectives on lived religion : practices transmission landscape - Weiss, Lara,; Staring, Nico,; Davies, Huw Twiston, (Papers on archaeology of the Leiden Museum of Antiquities ;, 2019)
Religion in the ancient world, and ancient Egyptian religion in particular, is often perceived as static, hierarchically organised, and centred on priests, tombs, and temples. Engagement with archaeological and textual evidence dispels these beguiling if superficial narratives, however. Individuals and groups continuously shaped their environments, and were shaped by them in turn. This volume explores the ways in which this adaptation, negotiation, and reconstruction of religious understandings took place. The material results of these processes are termed 'cultural geography'. The volume examines this 'cultural geography' through the study of three vectors of religious agency: religious practices, the transmission of texts and images, and the study of religious landscapes." - Back cover